2021
DOI: 10.1002/adfm.202009602
|View full text |Cite
|
Sign up to set email alerts
|

Skin Electronics: Next‐Generation Device Platform for Virtual and Augmented Reality

Abstract: Virtual reality (VR) and augmented reality (AR) are overcoming the physical limits of real‐life using advances in devices and software. In particular, the recent restrictions in transportation from the coronavirus disease 2019 (COVID‐19) pandemic are making people more interested in these virtual experiences. However, to minimize the differences between artificial and natural perception, more human‐interactive and human‐like devices are necessary. The skin is the largest organ of the human body and interacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
77
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(79 citation statements)
references
References 496 publications
(327 reference statements)
0
77
0
Order By: Relevance
“…The force feedback on the finger consists of normal haptic feedback to represent the force applied perpendicular to the finger surface and shear haptic feedback to represent slip and pull on the surface of the object. Recently, studies of the three-axis haptic feedback have been reported for more intuitive haptic feedback during teleoperation [11,21,22]. Leroy et al published a device that can generate haptics in both vertical and lateral directions using electrostatic forces [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The force feedback on the finger consists of normal haptic feedback to represent the force applied perpendicular to the finger surface and shear haptic feedback to represent slip and pull on the surface of the object. Recently, studies of the three-axis haptic feedback have been reported for more intuitive haptic feedback during teleoperation [11,21,22]. Leroy et al published a device that can generate haptics in both vertical and lateral directions using electrostatic forces [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies of the three-axis haptic feedback have been reported for more intuitive haptic feedback during teleoperation [11,21,22]. Leroy et al published a device that can generate haptics in both vertical and lateral directions using electrostatic forces [21]. Although hydrolytic forces were combined, it was a limitation of the device that the maximum lateral force was only 5 mN and the displacement was less than 1 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Pham and Stuerzlinger propose comparing the different controllers, focusing on the flexibility in using the 3D pen for VR and AR applications [105]. Electronic skins have recently been investigated as one of the most promising device solutions for future VR/AR devices [106], while the ARtention project [107] illustrates how input information can come directly from retinal motion. Finally, the MARVIS project proposes integrating HMDs and mobile devices for optimized data management in augmented reality [108].…”
Section: Network Connectivitymentioning
confidence: 99%
“…On‐skin digitalization is to transform multidimensional epidermal physiological signals into computer‐sensible digital language, streamlining the concept of the “human to device to cyberspace” platform. It aimed at making computers to interact with human in physical reality, at the same time adapting to the shape and mechanical characteristics of human skins 1 . The whole platform for on‐skin digitalization is divided into two parts, input sensing parts and integrated data processing systems.…”
Section: Introductionmentioning
confidence: 99%